1972
DOI: 10.1128/jvi.9.5.851-856.1972
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Polyvalent Bacteriophage for Escherichia coli, Klebsiella pneumoniae , and Aerobacter aerogenes

Abstract: A lytic bacteriophage isolated from sewage was found to attack strains of Aerobacter aerogenes, Escherichia coli, and Klebsiella pneumoniae, but not members of the genera Salmonella, Proteus, and Serratia. The phage, designated rmp, contained deoxyribonucleic acid with a 50%"c guanine plus cytosine ratio and a molecular weight of 23.1 X 101 daltons. Single-step growth experiments of rmp plated at 37 C on A. aerogenes A2 gave a mean latent period of 20 min, an average burst size of 103 plaque-forming units/infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In this study, E. faecalis phages infected and replicated in both E. faecalis and E. faecium. Characteristics of polyvalent phages (or broad-host-range phages), which are able to infect more than one species of bacteria, have previously been observed in certain bacteriophages (Souza et al 1972;Jensen et al 1998;Hamdi et al 2017) as well as enterococcal bacteriophages (Santiago-Rodriguez et al 2013). However, these polyvalent characteristics are unlikely to affect the application of bacteriophages for microbial source tracking.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, E. faecalis phages infected and replicated in both E. faecalis and E. faecium. Characteristics of polyvalent phages (or broad-host-range phages), which are able to infect more than one species of bacteria, have previously been observed in certain bacteriophages (Souza et al 1972;Jensen et al 1998;Hamdi et al 2017) as well as enterococcal bacteriophages (Santiago-Rodriguez et al 2013). However, these polyvalent characteristics are unlikely to affect the application of bacteriophages for microbial source tracking.…”
Section: Discussionmentioning
confidence: 92%
“…pneumoniae –phage combination from the caecal effluent of a healthy woman, and the implications of our findings in relation to gastrointestinal microbial ecology and the potential of the human gut as a source of phages with therapeutic uses. Previous studies describing the isolation of lytic phages against K. pneumoniae have reported recovery of these entities from wastewater, seawater, sewage and sewage-contaminated water samples, but never directly from gastrointestinal contents ( Souza, Ginoza & Haight, 1972 ; Kumari, Harjai & Chhibber, 2009 ; Kumari, Harjai & Chhibber, 2010a ; Drulis-Kawa et al, 2011 ; Hung et al, 2011 ; Cui et al, 2012 ; Hsu et al, 2013 ; Karumidze et al, 2013 ; Jamal et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…of different hosts of the same genus or between different genera are common (1,13). In dairy microbiology it is frequently observed that temperate phages for one species are able to infect other species either in a virulent or a temperate manner (11).…”
Section: Resultsmentioning
confidence: 99%